Correlation between PD-L1 expression ON CTCs and prognosis of patients with cancer: a systematic review and meta-analysis. (1st January 2021) - Kong, Defeng; Zhang, Wen; Yang, Zhenrong; Li, Guoliang; Cheng, Shujun; Zhang, Kaitai; Feng, Lin
ABSTRACT: Circulating tumor cells (CTCs) are considered to be related to the prognosis of cancer patients. CTC is a powerful indicator for recurrence or metastasis. The relationship, however, between the expression of programmed cell death receptor ligand 1 (PD-L1) on CTCs in peripheral blood and the prognosis, is still controversial. Here, we conducted a meta-analysis to evaluate its prognostic value. A total of 20 articles were screened from PubMed, Embase, Cochrane, China National Knowledge Internet (CNKI) and WanFang Database, and the Hazard Ratio (HR) along with 95% confidence intervals (CIs) of each article were combined to study the relationship between PD-L1 expression on CTCs and prognosis. The expression of PD-L1 on CTCs in the peripheral blood of cancer patients is associated with poor prognosis. The pooled HRs for overall survival (OS) in cancer patients were 1.85 (95% CI, 1.29–2.66, P = .001). The pooled HRs for progression-free survival (PFS) in cancer patients were 1.50 (95% CI, 1.12–2.01; P = .007). This is the first meta-analysis to clarify the expression of PD-L1 on CTCs at baseline affects the prognosis of cancer patients. Patients with CTCs expressing PD-L1 had a shorter survival time than patients with CTCs not expressing PD-L1.